Enhancing Students’ Speaking Skill through Gallery Walk Technique - Farrah Zakiyah Anwar (Register Journal, 2015)
The aims of this research are (1) to describe the procedure of enhancing students’ speaking skill by “gallery walk” technique at the first grade students of SMA Muhammadiyah (plus) Salatiga in academic year 2014/2015. (2) to find out whether the “gallery walk” technique can enhance students’ speaking skill or not and (3) to find out the extent of the use of “gallery walk” technique enhancing students’ speaking skill. The research method that is used in this research is classroom action reserach. The subjects of the research were 34 students in grade X at SMA Muhammadiyah (plus) Salatiga. The researcher uses two cycles; each cycle consists of planning, action, observation and reflection. The result of this research shows that there is an enhancement of the students’ speaking skill using “gallery walk” technique. It can be seen from T-Test calculating in cycle I is 5.09 and cycle II 6.70; T-Table with N = 34 is 2.035. And also the increasing students’ mean score in percentage from cycle I to cycle II with the standardized score (the minimum of passing criteria) is 75,  At the cycle I is 55.88% students and 82.35% in the cycle II. The increasing of score in percentage from cycle I to cycle II is 26.47 %. This indicates that by applying “gallery walk” technique, the students’ speaking skill can be enhanced.